Volume 2: Turbo Expo 2003 2003
DOI: 10.1115/gt2003-38169
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Instabilities in Liquid Fueled Combustors by Variation of Fuel Spray Properties

Abstract: This paper describes an experimental investigation of the feasibility of using “slow” active control approaches, which change liquid fuel spray properties, to suppress combustion instabilities. The objective of this control approach is to break up the feedback between the combustion process heat release oscillations and the combustor oscillations that drives the instability by changing the characteristics of the combustion process (i.e., characteristic combustion time). To demonstrate the feasibility of such c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Yu et al [10] successfully applied effervescent atomization to mitigate kerosene combustion instability in a supersonic model combustor. Lee et al [11] also demonstrated that by changing the spray characteristics, it is possible to significantly dampen combustion instabilities. These methods are necessary to a greater extent for heavy fuel applications where effervescent atomization and heating to reduce viscosity is common.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [10] successfully applied effervescent atomization to mitigate kerosene combustion instability in a supersonic model combustor. Lee et al [11] also demonstrated that by changing the spray characteristics, it is possible to significantly dampen combustion instabilities. These methods are necessary to a greater extent for heavy fuel applications where effervescent atomization and heating to reduce viscosity is common.…”
Section: Introductionmentioning
confidence: 99%